An efficient ML approach to detect brain tumor using MRI images - Muktadir, MD. Arafat; Ullah, A.S.M Rahmat; Hossain, Emdad; Islam, MD. Jubayer; Munny, Tanjila Akter (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.